CYP2D6 copy number determination using digital PCR - Wang, Wendy Y.; Lin, Lancy; Boone, Erin C.; Stevens, Junko; Gaedigk, Andrea (Frontiers in Pharmacology, 2024)
Background: CYP2D6 testing is increasingly used to guide drug therapy and thus, reliable methods are needed to test this complex and polymorphic gene locus. A particular challenge arises from the detection and interpretation of structural variants (SVs) including gene deletions, duplications, and hybrids with the CYP2D7 pseudogene. This study validated the Absolute Q platform for digital PCR-based CYP2D6 copy number variation (CNV) determination by comparing results to those obtained with a previously established method using the QX200 platform. In addition, protocols for streamlining CYP2D6 CNV testing were established and validated including the “One-pot” single-step restriction enzyme digestion and a multiplex assay simultaneously targeting the CYP2D6 5’UTR, intron 6, and exon 9 regions. Methods: Genomic DNA (gDNA) samples from Coriell (n=13) and from blood, saliva, and liver tissue (n=17) representing 0 – 6 copies were tested on the Absolute Q and QX200 platforms. Custom TaqMan™ copy number (CN) assays targeting CYP2D6 the 5’UTR, intron 6, and exon 9 regions and a reference gene assay (TERT or RNaseP) were combined for multiplexing by optical channel. In addition, two digestion methods (One-pot digestion and traditional) were assessed. Inconclusive CN values on the Absolute Q were resolved using an alternate reference gene and/or diluting gDNA. Results: Overall, results between the two platforms and digestions methods were consistent. The “One-pot” digestion method and optically multiplexing up to three CYP2D6 regions yielded consistent result across DNA sample types and diverse SVs, reliably detecting up to 6 gene copies. Rare variation in reference genes were found to interfere with results and interpretation, which were resolved by using a different reference. Conclusions: The Absolute Q produced accurate and reliable CYP2D6 copy number results allowing for a streamlined and economical protocol using One-pot digestion and multiplexing three target regions. Protocols are currently being expanded to other pharmacogenes presenting with SVs/CNVs.